2021
DOI: 10.3390/s21051607
|View full text |Cite
|
Sign up to set email alerts
|

A Video-Based Technique for Heart Rate and Eye Blinks Rate Estimation: A Potential Solution for Telemonitoring and Remote Healthcare

Abstract: Current telemedicine and remote healthcare applications foresee different interactions between the doctor and the patient relying on the use of commercial and medical wearable sensors and internet-based video conferencing platforms. Nevertheless, the existing applications necessarily require a contact between the patient and sensors for an objective evaluation of the patient’s state. The proposed study explored an innovative video-based solution for monitoring neurophysiological parameters of potential patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…is indicates that the pilot SA level cannot be effectively characterized by eyetracking metrics in such scenes based on the current research results. To effectively monitor the evolution of the pilot's SA cognitive states through physiological indicators in scene 1, scene 2, and scene 5, multiple indicators are needed for further consideration, such as heart rate variability (HRV) [37], electrodermal activity (EDA) [38], electromyography (EMG) [39], and electroencephalogram (EEG) [40].…”
Section: Correlation Evaluationmentioning
confidence: 99%
“…is indicates that the pilot SA level cannot be effectively characterized by eyetracking metrics in such scenes based on the current research results. To effectively monitor the evolution of the pilot's SA cognitive states through physiological indicators in scene 1, scene 2, and scene 5, multiple indicators are needed for further consideration, such as heart rate variability (HRV) [37], electrodermal activity (EDA) [38], electromyography (EMG) [39], and electroencephalogram (EEG) [40].…”
Section: Correlation Evaluationmentioning
confidence: 99%
“…The other purpose of filtering is to emphasise the heartbeat peaks (QRS process) of the ECG signals so that the distance between consecutive peaks can be measured (i.e. each R peak corresponds to a heartbeat) [ 51 ]. Heart rate and heart rate variability values can be estimated once these steps are completed.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced HRV, on the other hand, indicates that the body's stress response is not optimal, potentially exacerbating the negative effects of chronic stress and increasing the risk of stress-related medical conditions. Previous studies reported that HRV indices, as provided by telemedicine and remote healthcare applications [ 51 ] were significantly reduced in patients with depression [ 31 , 53 ] and anxiety disorders, including generalised anxiety disorder (GAD), social anxiety disorder, panic disorder and post-traumatic stress disorder [ 16 , 32 ]. Thus, we can conclude from a number of studies on HRV and mental illness that lower HRV in patients with mental illness is associated with poorer cardiovascular health outcomes and a variety of vascular diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The camera measurement of human physiological signals has gained considerable interest in the research community in recent years. The monitoring of vital signals such as heart rate (HR), heart rate variability (HRV), respiration rate (RR), oxygen saturation (SpO2) or blood volume pulse (BVP) is crucial in the assessment of the physical and mental human state, and its potential applications [1,13,28]. Traditionally, physiological signals are acquired using continuous bio-signal monitoring devices, which typically require physical contact between the sensor and the skin.…”
Section: Introductionmentioning
confidence: 99%